Microporous Lead-Organic Framework for Selective CO2 Adsorption and Heterogeneous Catalysis - Almáši, Miroslav; Zeleňák, Vladimír; Gyepes, Róbert; Bourrelly, Sandrine; Opanasenko, Maksym V; Llewellyn, Philip L; Čejka, Jiří (Inorganic chemistry, 2018)
A novel microporous metal-organic framework, {[Pb4(μ8-MTB)2(H2O)4]·5DMF·H2O}n (1; MTB = methanetetrabenzoate and DMF = N,N'-dimethylformamide), was successfully synthesized by a solvothermal reaction and structurally characterized by single-crystal X-ray diffraction. The framework exhibits a unique tetranuclear [Pb4(μ3-COO)(μ2-COO)6(COO)(H2O)4] secondary building unit (SBU). The combination of the SBU with the tetrahedral symmetry of MTB results in a three-dimensional network structure, with one-dimensional jarlike cavities having sizes of about 14.98 × 7.88 and 14.98 × 13.17 Å2 and propagating along the c axis. Due to the presence of four coordinately unsaturated sites per one metal cluster, an activated form of compound 1 (i.e., desolvated form denoted as 1') was tested in gas adsorption and catalytic experiments. The studies of gas sorption revealed that 1' exhibits a surface area (Brunauer-Emmett-Teller) of 980 m2·g-1. This value is the highest reported for any compound from the MTB group. Interactions of carbon dioxide (CO2) molecules with the framework, confirmed by density functional theory calculations, resulted in high CO2 uptake and significant selectivity of CO2 adsorption with respect to methane (CH4) and dinitrogen (N2) when measured from atmospheric pressure to 21 bar. The high selectivity of CO2 over N2 is mostly important for capturing CO2 from the atmosphere in attempts to decrease the greenhouse effect. Moreover, compound 1' was tested as a heterogeneous catalyst in Knoevenagel condensation of active methylene compounds with aldehydes. Excellent catalytic conversion and selectivity in the condensation of benzaldehyde and cyclohexanecarbaldehyde with malononitrile was observed, which suggests that accessible lead(II) sites play an important role in the heterogeneous catalytic process.